A de novo chromosome-scale assembly of the Lablab purpureus genome - Pootakham, Wirulda; Somta, Prakit; Kongkachana, Wasitthee; Naktang, Chaiwat; Sonthirod, Chutima; U-Thoomporn, Sonicha; Yoocha, Thippawan; Phadphon, Poompat; Tangphatsornruang, Sithichoke (Frontiers in Plant Science, 2024)
Lablab (Lablab purpureus (L.) Sweet), an underutilized tropical legume crop, plays a crucial role in global food and nutritional security. To enhance our understanding of its genetic makeup towards developing elite cultivars, we sequenced and assembled a draft genome of L. purpureus accession PK2022T020 using a single tube long fragment read (stLFR) technique. The preliminary assembly encompassed 367 Mb with a scaffold N50 of 4.3 Mb. To improve the contiguity of our draft genome, we employed a chromatin contact mapping (Hi-C) approach to obtain a pseudochromosome-level assembly containing 366 Mb with an N50 length of 31.1 Mb. A total of 327.4 Mb had successfully been anchored into 11 pseudomolecules, corresponding to the haploid chromosome number in lablab. Our gene prediction recovered 98.4% of the highly conserved orthologs based on the Benchmarking Universal Single-Copy Orthologs (BUSCO) analysis. Comparative analyses utilizing sequence information from single-copy orthologous genes demonstrated that L. purpureus diverged from the last common ancestor of the Phaseolus/Vigna species approximately 27.7 million years ago. A gene family expansion analysis revealed a significant expansion of genes involved in responses to biotic and abiotic stresses.Our high-quality chromosome-scale reference assembly provides an invaluable genomic resource for lablab genetic improvement and future comparative genomics studies among legume species.